2011
DOI: 10.1021/tx200126r
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic Caffeic and Ferulic Acid Derivatives Presenting Cytotoxicity against Human Breast Cancer Cells

Abstract: In the present work, lipophilic caffeic and ferulic acid derivatives were synthesized, and their cytotoxicity on cultured breast cancer cells was compared. A total of six compounds were initially evaluated: caffeic acid (CA), hexyl caffeate (HC), caffeoylhexylamide (HCA), ferulic acid (FA), hexyl ferulate (HF), and feruloylhexylamide (HFA). Cell proliferation, cell cycle progression, and apoptotic signaling were investigated in three human breast cancer cell lines, including estrogen-sensitive (MCF-7) and inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 53 publications
3
82
0
Order By: Relevance
“…At the administered dosages, ferulic acid was not carcinogenic (Kaul and Khanduja, 1998;Balakrishnan et al, 2008;Alias et al, 2009;Baskaran et al, 2010). Moreover, in human breast cancer (T47D) cells, ferulic acid inhibited proliferation at an IC 50 of 2.3 nM (Kampa et al, 2004), although inhibition of cell proliferation and apoptosis could not be reproduced in other human breast cancer cell lines at ferulic acid concentrations of up to 75 mM (Serafim et al, 2011). At concentrations of 150-1500 mM, however, ferulic acid was able to reduce cell viability in cultured rat hepatoma (HTC) cells (Maistro et al, 2011).…”
Section: B Pharmacokinetics and Pharmacodynamics Of Curcumin Catabolmentioning
confidence: 99%
“…At the administered dosages, ferulic acid was not carcinogenic (Kaul and Khanduja, 1998;Balakrishnan et al, 2008;Alias et al, 2009;Baskaran et al, 2010). Moreover, in human breast cancer (T47D) cells, ferulic acid inhibited proliferation at an IC 50 of 2.3 nM (Kampa et al, 2004), although inhibition of cell proliferation and apoptosis could not be reproduced in other human breast cancer cell lines at ferulic acid concentrations of up to 75 mM (Serafim et al, 2011). At concentrations of 150-1500 mM, however, ferulic acid was able to reduce cell viability in cultured rat hepatoma (HTC) cells (Maistro et al, 2011).…”
Section: B Pharmacokinetics and Pharmacodynamics Of Curcumin Catabolmentioning
confidence: 99%
“…Vanillic acid, a vegetable phenolic compound, is a strong antioxidant (Erdem et al, 2012). Moreover, ferulic acid enhances radiation effects by increasing lipid peroxidative markers in two cervical cancer cell lines, namely HeLa and ME-180, in vitro (Karthikeyan et al, 2011;Serafim et al, 2011). An in vivo model has shown that resveratrol has not only anti-inflammatory, anti-oxidant, anti-mutation, anti-proliferation and anticell cycle activities but also induces apoptosis and has synergistic effects with chemotherapeutic drugs (Frampton et al, 2010;Hahnvajanawong et al, 2011).…”
Section: 449 Cytotoxic Effects Of Phytophenolics From Caesalpinia MImentioning
confidence: 99%
“…Plant phytochemicals have been reported to prevent a number of diseases, including cancer, cardiovascular disease, infection and inflammation. In vitro studies have revealed that some phytochemicals, such as gallic acid (Gali et al, 1991;Ohno et al, 2001;Kim 2007;You et al, 2010;Lu et al, 2010), caffeine (Kawano et al, 2012), vanillic acid (Erdem et al, 2012), and ferulic acid (Karthikeyan et al, 2011;Serafim et al, 2011), are cytotoxic to cell lines. An in vivo model has shown that resveratrol not only has anti-inflammatory, anti-oxidative, anti-mutation, anti-proliferative, and anti-cell cycle properties but also induces apoptosis and has synergistic effects with chemotherapeutic drugs (Frampton et al, 2010;Hahnvajanawong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The main sources of ferulic acid are foods such as wheat bran, but also coffee, apples, artichokes, peanuts, oranges, and pineapples. Animal studies and in vitro studies suggest that ferulic acid may have direct antitumour activity against breast and colon cancer (53)(54)(55). Ferulic acid has a significant role in the inhibition of abnormal cell proliferation in cancer cells occurring in induced carcinogenesis due to its modulatory effect on pro-apoptotic genes p53 and bcl-2 expression (56).…”
Section: Ferulic Acidmentioning
confidence: 99%